Pelatihan Teknologi Pengeleman kayu dalam Air untuk Sampan Nelayan - Mansyur Hasbullah (Faculty of Engineering UNHAS, 2020)
The sampan as a transportation vehicle for transporting fish from fishing boats serves to collect and catch fish in the ground seas. These fish caught by fishermen are brought ashore to be marketed. With a carrying capacity of about 0.05 GT or 0.03 GT generally without a propulsion engine, the role of the canoe is very strategic because without its existence as a fishing boat aide there will be a risk to the cargo in the boat. From the results of monitoring in the field shows that sometimes sampan (canoe) experience leakage when operating transporting fish. For repairs to the leather boat the boat must be carried ashore with an empty load. The wood gluing technology in water will be able to overcome this condition, because the gluing of the canoe is carried out when the load is in the canoe, without having to empty / move the cargo. The performance of this propant glue will be known if there is a relationship between different wood surface areas and varying thicknesses of glue causing different shear stresses. From the results of testing on wood components that show that the thickness of the glue between 0.01 cm to 0.02 cm with a gluing area (2.4 x 1.9 cm) compared to the thickness of the glue and a greater gluing surface area has shown superiority and efficiency, because with low thickness is able to withstand shear stress of 662.5 kg / cm4 and can glue and connect the bark of the sampan cm2 which in a continuous drying time ± 3 hours from normal water and air conditions.